Cognitive Behavioral Therapy to Improve Self-Efficacy and Reduce Academic Procrastination (Jurnal Bimbingan Konseling, 2020)
Self-efficacy is a considerable predictor in improving university students’ academic achievement. Therefore, it is important for university counselors to decide the right treatment for self-efficacy and academic procrastination matters. Regarding this issue, this study was attempted to identify and analyze the effectiveness and effectiveness degree of CBT and self-talk technique in improving self-efficacy and reducing academic procrastination behavior. The subjects involved were 16 university students chosen using purposive sampling technique. Their data of self-efficacy and academic procrastination were collected using College Academic Self-efficacy scale and Tuckman Procrastination scale. Upon the analysis, it was found that the use of CBT with self-talk technique was effective to improve self-efficacy and reduce academic procrastination. These findings prove that the use of CBT with self-talk technique is effective to improve self-efficacy and reduce academic procrastination